The Effect of User's Participation Motives on the Web Site Branding of Tehran University of Medical Sciences - Mashallah Torabi; Sara Naeimi; Elnaz Vahedi; Hamideh Hamidi (Tehran University of Medical Sciences, 2024)
Background and Aim: Educating the audience is one of the things that can affect their mental perception of the usefulness and ease of utilizing technology. Due to the lack of knowledge about the unique features and ease of use of Tehran University of Medical Sciences website, some audiences prefer to use the old website and do not accept the changes on the university website well. This research was conducted with the aim of comparing the two methods of face-to-face training and clip training in accepting information technology changes on the university website and evaluating the audience's awareness of branding features on the web. Materials and Methods: There were 90 people who participated in this study, 45 of whom received face-to-face training and 45 of them received training about site changes through video clips. Research data collection was done based on Davis questionnaire and data analysis was done using SPSS and Padprism graph software. To compare a quantitative variable in more than two groups, one-way analysis of variance test or Kruskal-Wallis test and also, and also, one-way ANCOVA test were used to check the difference between groups before and after training. Results: In face-to-face training, variables such as awareness, usefulness and perceived ease of use, as well as attitude and performance regarding the use of information technology before and after face-to-face training or clip did not have significant differences. Conclusion: Examining the effectiveness of the teaching methods in this project will help the public relations of the university to act quickly for the changes that will occur in the field of web branding in the future, in terms of preparing and accompanying the audience.